Does Nasal Surgery Affect Right Ventricular Myocardial Functions at the Tissue Level in Patients with Nasal Septum Deviation? - Ziya Simsek (Journal of Clinical Medicine, 2018)
Objective: One of the most common causes of upper airway obstruction in adults is nasal septum deviation (NSD). The chronic hypoxia caused by this obstruction gradually leads to increased pulmonary vascular resistance, pulmonary hypertension (PHT), and right ventricular (RV) failure. The purpose of this study was to determine changes in RV myocardial functions at the tissue level before, and after surgery in patients with NSD. Subjects and Methods: Fifty-eight patients with symptoms of nasal obstruction and snoring were included in this observational study. Preoperative and postoperative third-month peripheral arterial oxygen saturation (SpO2), and RV systolic and diastolic functions measured by pulmonary artery systolic pressure (PASP), tissue Doppler parameters, and speckle tracking echocardiography (STE) were studied in these patients. Results: We observed a very significant decrease in PASP in the postoperative period (32.54 ± 5.24 mmHg vs. 24.22 ± 4.55 mmHg, p = 0.001). Postoperative SpO2 values, measured at room temperature also increased significantly (93.5 ± 0.82% vs. 95.6 ± 0.79%, p = 0.001). There was a significant improvement after surgery in RV systolic functions, represented by global longitudinal strain (GLS) (21.12 ± 2.07 vs. 22.49 ± 1.89, p = 0.013) and systolic global longitudinal strain rate (GLSRs) (1.30 ± 0.12 vs. 1.38 ± 0.13, p = 0.015). No significant differences in terms of RV diastolic function parameters were detected, including the RV early diastolic global longitudinal strain rate (GLSRe) (1.56 ± 0.21 vs. 1.55 ± 0.26, p = 0.86) and RV late diastolic global longitudinal strain rate (GLSRa) (0.88 ± 0.19; 0.89 ± 0.18, p = 0.76). Conclusion: This study was performed with an advanced technique capable of tissue level examination. The findings demonstrated significant improvement in both chronic hypoxia and RV systolic myocardial functions, measured at the tissue level after nasal surgery.